Mediating effect of competitive advantage on the relationship between corporate strategy and business performance - Samad, Sarminah (International Journal of Engineering and Technology, 2018)
This study examined the effect of competitive advantage on the relationship between corporate strategy and business performance. It also examined the effect of corporate strategy and competitive advantage on business performance. A total of 222 hotel managers participated in this study based on self-administered questionnaires. Smart Partial Least Squares (PLS) analysis was employed to analyze the obtained data. The study revealed that corporate strategy has a positive and significant effect on business performance and competitive advantage.Â Competitive advantage was also found to have a positive and significant effect on business performance. The study revealed that competitive advantage has significantly mediated the relationship between corporate strategy and business performance. The study provides support for both practical and theoretical reference values.Â